Introduction to software for chemical engineers - Martín, Mariano Martín (CRC Press/Taylor and Francis Group, 2018)
"This book serves as a quick guide to the use of various computer packages for chemical engineering applications. It covers a range of computer packages from Excel and general mathematical packages such as MATLAB and Mathematica to process simulators, CHEMCAD and ASPEN, equation-based modeling languages, gProms, optimization software such as GAMS, and specialized software like CFD or DEM codes. The new edition offers a wider view of packages including Python and Julia and open source software and includes complete examples in ASPEN Plus. It also adds ANSYS Fluent to CFD codes and discusses Engineering Equation Solver"--